Advances in passive cooling - Santamouris, M. 1956- (Earthscan, 2007)
Following a rapid increase in the use of air conditioning in buildings of all types, the energy demand for powering such devices has become a significant cause for concern. Passive cooling is increasingly being thought of as the best alternative to air conditioning. This book offers the latest knowledge and techniques on passive cooling, enabling building professionals to understand the state of the art and employ relevant new strategies. With separate chapters on comfort, urban microclimate, solar control, ventilation, ground cooling and evaporative and radiative cooling, this authoritative te.
Keywords: Solar air conditioning -- Passive systems.; elektronické knihy; electronic books